Rainfall performance at the Institute of Animal Science in Cuba during the period 1970-2009 as basis for the strategic management of pastures - ?lvarez, Adri?n; Herrera, Rafael Segundo; Noda, Aida C.; D?az, Laisurys (Cuban Journal of Agricultural Science, 2012)
Rainfall performance in the farm of the Institute of Animal Science (ICA) in Cuba during the period 1970-2009 was studied with data recorded at the agro-meteorological station. The methodology of analysis of seasonal series was applied and the performance of its components: seasonal variations, trend, cyclicity and random component of the time series were studied. It was confirmed that the seasonal character of rainfall was maintained each year, but showed stability during the last decade, as well as decrease of the minimum and maximum values. There was a very high variability and it was confirmed by the analysis of the coefficients of variation, which reached values above 41% in all months, particularly, in the poor rainy period, with average fluctuations of 200 mm. Also in this stage there was a decrease in the amount of rainfall of 324 mm in the period 1970-1980 to 225 mm presently. It is foreseen that this decrease will continue and that the difference between periods will increase, with a probability of 1105.7 mm for 95%. In general, rainy days also showed a decreasing trend. Regarding rainfall cyclicity at ICA, the duration was variable. It can be concluded that the high rainfall inter-annual variability, the inequality of its distribution throughout the year and the decrease of the rainy days favor the instability of these events at ICA?s farm. Key words: time series, rainfall, animal production